2021
DOI: 10.1073/pnas.2024942118
|View full text |Cite
|
Sign up to set email alerts
|

Cell contact guidance via sensing anisotropy of network mechanical resistance

Abstract: Despite the ubiquitous importance of cell contact guidance, the signal-inducing contact guidance of mammalian cells in an aligned fibril network has defied elucidation. This is due to multiple interdependent signals that an aligned fibril network presents to cells, including, at least, anisotropy of adhesion, porosity, and mechanical resistance. By forming aligned fibrin gels with the same alignment strength, but cross-linked to different extents, the anisotropic mechanical resistance hypothesis of contact gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 59 publications
5
41
0
Order By: Relevance
“…As noted previously, it was recently demonstrated that human dermal fibroblasts exhibit stronger contact guidance in gels that possess a larger anisotropy of mechanical resistance [8]. In that study, network mechanical resistance was measured using active microrheology, the oscillation of 5 µm microspheres entrapped in the network.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…As noted previously, it was recently demonstrated that human dermal fibroblasts exhibit stronger contact guidance in gels that possess a larger anisotropy of mechanical resistance [8]. In that study, network mechanical resistance was measured using active microrheology, the oscillation of 5 µm microspheres entrapped in the network.…”
Section: Discussionmentioning
confidence: 87%
“…While fibrin and collagen gels share many similarities as highly hydrated fibrillar networks, and fibroblasts exhibit contact guidance in both when aligned [8,29], they are not identical in terms of detailed geometrical factors, such as fibril diameter, density and connectivity. Thus, it is notable that this model predicts quantitative differences with varied fibre mechanical response (nonlinear stiffening parameter, B ) and different fibre connectivity (Delaunay versus Voronoi), but the qualitative trends of S with Ω xx are similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations